The St. Petersburg paradox with state dependent linear utility functions for monetary returns. A note - Somdeb Lahiri (Managerial Economics)
In the experiment underlying the St. Petersburg paradox, we use state-dependent linear utility functions for money with a countably infinite set of states of nature to show that a potential participant will be willing to pay no more than a finite sum of money to participate in the experiment.